Ghrelin Receptor Regulates Appetite and Satiety during Aging in Mice by Regulating Meal Frequency and Portion Size but Not Total Food Intake. Issue 9 (2nd July 2014) - Lin, Ligen; Nuotio-Antar, Alli M.; Ma, Xiaojun; Liu, Feng; Fiorotto, Marta L.; Sun, Yuxiang
Abstract: Aging is often associated with overweight and obesity. There exists a long-standing debate about whether meal pattern also contributes to the development of obesity. The orexigenic hormone ghrelin regulates appetite and satiety by activating its receptor, growth hormone secretagogue receptor (GHS-R). In mice, circulating ghrelin concentrations and brain GHS-R expression were shown to increase with aging. To assess whether GHS-R regulates feeding pattern during aging, we studied meal patterns for the following cohorts of male mice fed a normal unpurified diet: 1 ) 3–4 mo, young wild-type (WT) mice; 2 ) 3–4 mo, young Ghsr -null ( Ghsr −/− ) mice; 3 ) 12–14 mo, middle-aged WT (WT-M) mice; 4 ) 12–14 mo, middle-aged Ghsr −/− ( Ghsr −/− -M) mice; 5 ) 24–26 mo, old WT (WT-O) mice; and 6 ) 24–26 mo, old Ghsr −/− ( Ghsr −/− -O) mice. Although the total daily food intake of Ghsr −/− mice was similar to that of WT controls, Ghsr −/− -M and Ghsr −/− -O mice had 9% ( P = 0.07) and 16% ( P < 0.05) less body weight compared with WT-M and WT-O mice, respectively, primarily due to reduced fat mass ( P < 0.05, WT-M vs. Ghsr −/− -M and WT-O vs. Ghsr −/− -O). Intriguingly, Ghsr −/− -M mice ate larger meals (on average, Ghsr −/− -M mice ate 0.117 g/meal and WT-M mice ate 0.080 g/meal; P < 0.01) and took a longer time to eat ( Ghsr −/− -M, 196.0 s and WT-M, 128.9 s; P < 0.01), but ate less frequently ( Ghsr −/− -M, 31.0 times/d and WT-M, 42.3 times/d; P < 0.05) than WT-M controls. In addition, we found that expression of hypothalamic orexigenic peptides, neuropeptide Y ( NPY ) and agouti-related peptide ( AgRP ), was relatively lower in aged WT mice ( P = 0.09 for NPY and P = 0.06 for AgRP ), but anorexic peptide pro-opiomelanocortin ( POMC ) expression remained unchanged between the WT age groups. Interestingly, old Ghsr −/− mice had greater hypothalamic NPY expression (102% higher; P < 0.05) and AgRP expression ( P = 0.07) but significantly lower POMC expression ( P < 0.05) when compared with age-matched WT-O controls. Thus, our results indicate that GHS-R plays an important role in the regulation of meal pattern and that GHS-R ablation may modulate feeding behavior through the regulation of hypothalamic neuropeptides. Our results collectively suggest that ghrelin receptor antagonism may have a beneficial effect on metabolism during aging.